Perancangan Bisnis Digital Menggunakan Blogger Dan Media Sosial Untuk Meningkatkan Daya Tarik Penjualan Kue Putu Bambu Khas Medan - Siti Latifah; Intania Nur Wanri; Rizkia Anilva; Faradika (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
The rapid development of information and communication technology, especially in the digital era, has changed the business landscape significantly. MSMEs (Micro, Small and Medium Enterprises) are one of the sectors that need to adapt quickly to remain competitive and develop amidst increasingly fierce competition. Digital transformation is a necessity for MSMEs in order to optimize the potential and vast market opportunities in cyberspace. So the aim of making this report is to make a positive contribution in supporting the growth and sustainability of MSMEs in the digital era. The Digital Business course provides an opportunity for us as students to apply web design concepts and the latest technology.